Runoff‐generated debris flows: Observations and modeling of surge initiation, magnitude, and frequency. Issue 4 (18th October 2013) - Kean, Jason W.; McCoy, Scott W.; Tucker, Gregory E.; Staley, Dennis M.; Coe, Jeffrey A.
Abstract [1] Runoff during intense rainstorms plays a major role in generating debris flows in many alpine areas and burned steeplands. Yet compared to debris flow initiation from shallow landslides, the mechanics by which runoff generates a debris flow are less understood. To better understand debris flow initiation by surface water runoff, we monitored flow stage and rainfall associated with debris flows in the headwaters of two small catchments: a bedrock‐dominated alpine basin in central Colorado (0.06 km2) and a recently burned area in southern California (0.01 km2). We also obtained video footage of debris flow initiation and flow dynamics from three cameras at the Colorado site. Stage observations at both sites display distinct patterns in debris flow surge characteristics relative to rainfall intensity (I). We observe small, quasiperiodic surges at low I; large, quasiperiodic surges at intermediate I; and a single large surge followed by small‐amplitude fluctuations about a more steady high flow at high I. Video observations of surge formation lead us to the hypothesis that these flow patterns are controlled by upstream variations in channel slope, in which low‐gradient sections act as "sediment capacitors, " temporarily storing incoming bed load transported by water flow and periodically releasing the accumulated sediment as a debris flow surge. To explore this hypothesis, we develop a simple one‐dimensional morphodynamic model of a sediment capacitor that consists of a system of coupled equations for water flow, bed load transport, slope stability, and mass flow. This model reproduces the essential patterns in surge magnitude and frequency with rainfall intensity observed at the two field sites and provides a new framework for predicting the runoff threshold for debris flow initiation in a burned or alpine setting.